IMPLEMENTASI PROGRAM USAHA EKONOMI KELURAHAN-SIMPAN PINJAM HARAPAN BERSAMA - Septian, Andrico; Rusli, Zaili; R.F.S, Harapan Tua (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of the Economic Business Program of the Savings and Loans Harapan Bersama Village. This research is a qualitative type. The research informant was the chairperson of UEK-SP and his staff Lurah, Chair of LPM and Women Leaders. Data collection techniques are interviews, observation and documentation. Data analysts use interactive models ranging from data presentation, data reduction and conclusion drawing. The results of this study indicate that the implementation of UEK-SP in Kampung Melayu Village has not fully touched the community, the high arrears of loans by the community, namely the lack of awareness of the public to pay its debts, and the lack of optimal guidance and supervision activities.